1984
DOI: 10.1128/jcm.20.2.281-284.1984
|View full text |Cite
|
Sign up to set email alerts
|

Application of the peroxidase-antiperoxidase immunoassay to the identification of Salmonellae from pure culture and animal tissue

Abstract: The peroxidase-antiperoxidase immunoassay was developed by using selected Salmonella serotypes to evaluate its potential for use in diagnostic bacteriology. S. choleraesuis var. kunzendorf, S. dublin, and S. typhimurium were the test organisms. Strong specific staining with corresponding antiserum was achieved with smears of each Salmonella serotype oh microscope slides from formalinized cell suspensions, live broth cultures of clinical isolates, and tissue suspensions from the livers and spleens of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The staining results concerning bacterial morphology and distribution were principally comparable to descriptions found in the literature. 6 , 8 , 22-24 In the sections of lymph nodes including control sections (IgG - and buffer control), spots of brown pigment of approximately the same size as the expected immunohistochemical reaction product for S. Typhimurium were visible. Since these pigment granules were of similar size and color as the labelled bacteria, it was necessary to distinguish them from the microorganisms.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The staining results concerning bacterial morphology and distribution were principally comparable to descriptions found in the literature. 6 , 8 , 22-24 In the sections of lymph nodes including control sections (IgG - and buffer control), spots of brown pigment of approximately the same size as the expected immunohistochemical reaction product for S. Typhimurium were visible. Since these pigment granules were of similar size and color as the labelled bacteria, it was necessary to distinguish them from the microorganisms.…”
Section: Discussionmentioning
confidence: 93%
“…As microorganisms are at the limit of light microscopical detection and results may vary from slide to slide because of heterogeneous distribution of the bacteria in the tissue, histology is not the method of choice for routine diagnosis and quantification of bacterial infections in tissues. 22 One method routinely used to detect and quantify microbes is microbial plate counting. Interestingly, an organ-specific difference between results of our immunohistochemical labelling of S. Typhimurium and microbial plate counting done in the same trial by Kreuzer et al could be found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct use of antibodies as a rapid means of identifying Salmonella spp. in culture (8,9,11,13,14), clinical specimens (8,14), and foods (10) has been investigated previously; variable success, which seemed to depend on the specificity of the polyclonall) antibody and technique used, was seen in these studies. Svenungsson et al 14, for example, demonstrated the high (100%) specificity that is achievable with a monospecific 0-9 antiserum sample when used with immunofluorescence to detect Salmonella enteritidis organisms in fecal cultures.…”
Section: Discussionmentioning
confidence: 99%
“…However, immunohistological techniques are now frequently being used to demonstrate a variety of infectious agents as well as other tissue antigens in routinely processed material (DUCATELLE et al, 1982;MORGAN, 1977;OHMAN et al, 1981;PALMER et al, 1985;TURFREY, 1985). Most infectious agents so far demonstrated in formalin-fixed and paraffin-embedded tissues have been viruses, but immunohistological identification of bacteria is also feasible in some bacterial diseases (MCRILL et al, 1984;ROGERS, 1985). Immunohistology can be a major aid for diagnosis of those bacterial diseases caused by agents which d o not grow or do so poorly in usual isolation procedures or grow very…”
Section: Discussionmentioning
confidence: 99%